Stool sampling and DNA isolation kits affect DNA quality and bacterial composition following 16S rRNA gene sequencing using MiSeq Illumina platform - Videnska, Petra; Smerkova, Kristyna; Zwinsova, Barbora; Popovici, Vlad; Micenkova, Lenka; Sedlar, Karel; Budinska, Eva (Scientific reports, 2019)
Many studies correlate changes in human gut microbiome with the onset of various diseases, mostly by 16S rRNA gene sequencing. Setting up the optimal sampling and DNA isolation procedures is crucial for robustness and reproducibility of the results. We performed a systematic comparison of several sampling and DNA isolation kits, quantified their effect on bacterial gDNA quality and the bacterial composition estimates at all taxonomic levels. Sixteen volunteers tested three sampling kits. All samples were consequently processed by two DNA isolation kits. We found that the choice of both stool sampling and DNA isolation kits have an effect on bacterial composition with respect to Gram-positivity, however the isolation kit had a stronger effect than the sampling kit. The proportion of bacteria affected by isolation and sampling kits was larger at higher taxa levels compared to lower taxa levels. The PowerLyzer PowerSoil DNA Isolation Kit outperformed the QIAamp DNA Stool Mini Kit mainly due to better lysis of Gram-positive bacteria while keeping the values of all the other assessed parameters within a reasonable range. The presented effects need to be taken into account when comparing results across multiple studies or computing ratios between Gram-positive and Gram-negative bacteria.
Keywords: dospělí; lidé; Reproducibility of Results; Feces; reprodukovatelnost výsledků; sekvenční analýza DNA; Sequence Analysis, DNA; mladý dospělý; Healthy Volunteers; RNA, Ribosomal, 16S; lidé středního věku; Humans; fylogeneze; Reagent Kits, Diagnostic; grampozitivní bakterie; feces; DNA bakterií; gramnegativní bakterie; zdraví dobrovolníci pro lékařské studie; reagenční diagnostické soupravy; Adult; Gram-Negative Bacteria; vysoce účinné nukleotidové sekvenování; Young Adult; Gram-Positive Bacteria; DNA, Bacterial; Middle Aged; Phylogeny; High-Throughput Nucleotide Sequencing; RNA ribozomální 16S